Simulation and Optimization of Short Fiber Circumferential Orientation in Short-Fiber-Reinforced Composites Overflow Water-Assisted Injection Molded Tube - Haiying Zhou; Hesheng Liu; Tangqing Kuang; Qingsong Jiang; Zhixin Chen; Weiping Li (Advances in Polymer Technology)
The mechanical properties of the water-assisted injection molded tube can be enhanced by the increase in the short fiber circumferential orientation (SFCO). Thus, the numerical method verified by experiments is used to simulate the SFCO distribution in the overflow water-assisted injection molding (OWAIM), with the mechanism of short fiber orientation analyzed as well. The effect of parameters (filling time, melt temperature, mold temperature, delay time, water pressure, and water temperature) on the SFCO is explored by range analysis and variance analysis of the orthogonal experimental scheme. Moreover, both of artificial neural network (ANN) and genetic algorithm (GA) are used to model and optimize process parameters. Results show that the melt temperature, delay time, and water pressure are predominant parameters. The evolution of SFCO increases with the increase of melt temperature and water pressure, whereas the changes in delay time reverse. The value of the maximum SFCO tensor obtained by GA optimization is found to be 0.234.